(untitled) (Journal of the College of Basic Education, 2025)
The current study aims to identify (the effect of a counseling method (imposing the wrong concept) in reducing obsessive thoughts among female students of the College of Basic Education, Al-Mustansiriya University). To achieve the goal of the study, the researcher formulated the following hypotheses: 1- There is no statistically significant difference at the level (0.05) between the average of the female students of the experimental group who study the subject of psychological counseling and educational guidance in a counseling manner (imposing the wrong concept) and the average of the female students of the control group who study the same subject in the normal manner in the scores of the thoughts reduction test. Obsessiveness. 2- There is no statistically significant difference at the level (0.05) between the average of the female students of the experimental group who are studying the subject of psychological counseling and educational guidance using a counseling method (imposing the wrong concept) in the pre- and post-test of reducing obsessive thoughts. 3- There is no statistically significant difference at the level (0.05) between the average of the female students of the control group who are studying psychological counseling and educational guidance in the traditional way in the pre- and post-test of reducing obsessive thoughts. The researcher chose an experimental design for partial control with two groups: experimental and control. The two study groups were rewarded with a number of variables (chronological age calculated by month, first month’s test scores, IQ scale scores). The College of Basic Education, Guidance Department,